Perancangan Desain UI/UX Aplikasi Somnia untuk Manajemen Pola Tidur Berbasis Mobile - Kartika Dewi, Ni Putu Meita; Putra, Ida Ayu Gde Suwiprabayanti (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025, 2025)
Sleep is an essential basic need for human health and well-being. However, in the midst of a busy modern lifestyle, achieving ideal sleep becomes a challenge due to several factors. Consequently, lack of sleep can cause a negative impact on both physical and mental health. Based on these problems, this research aims to design the sleep management application "Somnia" using the prototype method. The application design is then evaluated using the System Usability Scale method. The evaluation results show that the average value of user satisfaction reaches 85.5, indicating that the design results is considered acceptable, with the adjective category being excellent, and received grade A. It was concluded, the design of the Somnia application is believed to have met user needs.